IMPLEMENTASI PEMBELAJARAN DENGAN KONSEP RAMAH ANAK DALAM MEMBANGUN EMPATI SISWA DI SEKOLAH DASAR - Hamidaturrohmah Hamidaturrohmah; Saidatul Irfana; Shahnaz Surayya (Tunas Nusantara, 2020)
Empathy is one of the abilities of a person who plays a major role in shaping human behavior so it is important to instill it from an early age. This study aims to analyze the form of implementation of learning with child-friendly concepts in increasing empathy for elementary school students. The research method used is descriptive qualitative case study type. This research was conducted at the Semai Jepara Elementary School. In collecting data using the method of observation, interviews, and documentation. The data analysis technique uses qualitative analysis which is inductive in nature. The results showed that there were two forms. First, a form of increasing empathy through the process of implementing learning with learning strategies such as sociodrama, service learning, and story telling. Second, increasing empathy through the form of activity programs carried out at SD Semai including club or extracurricular programs based on multiple intelligences, program for commemorating certain days, and also the final theme program. Based on the results of this study, it can be concluded that learning in elementary schools with child-friendly concepts can increase student empathyKeywords: Child Friendly Learning, Empathy, Elementary School Students